Swallows and Settlers The Great Migration from North China to Manchuria - Gottschang, Thomas R. (Michigan Monographs In Chinese Studies, 2020)
Between the 1890s and the Second World War, twenty-five million people traveled from the densely populated North China provinces of Shandong and Hebei to seek employment in the growing economy of China's three northeastern provinces, the area known as Manchuria. This was the greatest population movement in modern Chinese history and ranks among the largest migrations in the world. Swallows and Settlers is the first comprehensive study of that migration. Drawing methods from their respective fields of economics and history, the coauthors focus on both the broad quantitative outlines of the movement and on the decisions and experiences of individual migrants and their families. In readable narrative prose, the book lays out the historical relationship between North China and the Northeast (Manchuria) and concludes with an examination of ongoing population movement between these regions since the founding of the People's Republic in 1949.